VD_FINDINFO Décision / 2015 / 65 vom 23. Dezember 2014 - VD Tribunal cantonal (2014)
CLASSEMENT DE LA PROCÉDURE, CALOMNIE, CONTRAINTEDROIT PÉNAL | 174 CP, 181 CP, 310 CPP (CH), 393 al. 1 let. a CPP (CH)